Biotechnological Potential of Fungi From the Brazilian Amazon: A Systematic Review - Garcia Mendoza, Anita Yris (2022)
The Amazon Biome is known as the greatest biological diversity and forest richness of the planet, constitutes a source of great value for the search of new enzymatic extracts to be explored for biotechnological application. In this context, fungi are used in food production, in the pharmaceutical industry, in the biodegradation process, in the biological treatment of effluents, they act in the enzymatic activity, of industrial interest and biotransformation, they are also of great agricultural and ecological importance. Thus, the present work aimed to perform a systematic review on fungal biotechnology in the Brazilian Amazon, presenting works developed in the region, noting the period of inclusion in the last 10 years (2010-2020). It was verified the publication of 31 works of bibliographic productions on biotechnological applications. The productions on the theme of fungal biotechnology were infrequently comprehensive in the year 2010 until the year 2013. It was found that there was a following growth of stability of the theme's incidence in publications in the subsequent years, especially in the year 2017 until the year 2020. Based on the study conducted, it was verified the importance of different works that address the study of Biotechnology to obtain various substances through the manipulation of fungi, in order to obtain new technologies for the benefit of society and importance to the environment.